A Method for Multiple Attribute Decision Making Based on the Fusion of Multisource Information - F. W. Zhang; S. H. Xu; B. J. Wang; Z. J. Wu (Abstract and Applied Analysis)
We propose a new method for the multiple attribute decision making problem. In this problem, the decision making information assembles multiple source data. Two main advantages of this proposed approach are that (i) it provides a data fusion technique, which can efficiently deal with the multisource decision making information; (ii) it can produce the degree of credibility of the entire decision making. The proposed method performs very well especially for the scenario that there exists conflict among the multiple source information. Finally, a traffic engineering example is given to illustrate the effect of our method.